Ensino de professores para o uso de Instrução com Tentativas Discretas para crianças com Transtorno do Espectro Autista - Aporta, Ana Paula (2015)
Nowadays the number of people diagnosed with autism has been rising. For instance, in U.S.A, one in 68 children is diagnosed with autism spectrum disorder and, proportionally, there s an increasing effort towards training teachers to work with this population. Evidence based studies have been showing favorable outcomes of Applied Behavior Analysis (ABA) teaching techniques. One of them is called Discrete Trials Instruction (DTI), which is constituted of four parts: a) an instruction (discriminative stimulus), b) a prompt to help the child to respond correctly, c) a consequence for the response. Teachers generally conduct this teaching with one child at time and his/her curriculum is based on individualized evaluation. The current study is presented in two studies with the first aimed to replicate systematically Pollard et al. (2014) using a multiple baseline design among participants who were Brazilian university students. As a continuation, the second chapter aimed to evaluate the effectiveness of e-learning to teach interventions for children with autism based on ABA for special education teachers in a Brazilian institution for children with disabilities. In both studies the participants were implementing ITD freely baseline sessions, from the leaves of programs with description of target behaviors that should teach and materials needed for this education that were presented by the experimenter, then participants received one made computerized training four teaching modules to implement the ITD post-training sessions in the same manner baseline. Baseline sessions, training and post-training Study 1 were developed in a classroom at a university in São Paulo and sessions with children with ASD were developed in a special school in São Paulo. All sessions of Study 2 were developed in a classroom of the same school. Similar to Pollard et al. (2014) this study showed that the participants performed correctly DTI after computerized training. Participants took a mean of four hours to complete de four modules of training, and all of them showed 100% of correct responses on the test questions. These results indicate that the E-Learning Training can be a good option to teach people to conduct DTI.